Training of Trainers (ToT) Workshop on Indigenous and Local Trees-based Agroforestry Systems Course Module - Ekepu, David; Majaliwa, Jackson Gilbert Mwanjalolo; Nakayiwa, Florence Mayega (2023)
As part of the AICCRA, the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) are tasked to develop curricula and training materials to accelerate the mainstreaming of Climate Information Services (CIS) and Climate- Smart Agriculture (CSA) into University’s curricula in Africa. This report describes the activities of a training of trainers’ (ToT) workshop on Indigenous and local trees-based agroforestry systems course module, held on 11-14 April 2023. The overall objective of the training of trainers’ workshop was to increase awareness and scale adoption/integration of the module on Indigenous and local trees-based agroforestry systems across the RUFORUM Network and other non-AICCRA countries. 207 (Male=136; Female=71) participants from 91 universities in 28 countries attended the training. The participants indicated good satisfaction with the training of trainers on Indigenous and local trees-based agroforestry systems. As a way forward to strengthen awareness creation, there is a need to strengthen the pedagogy of the training module for example using case studies of successful CSA/CIS innovations generated under AICCRA.